2003
DOI: 10.1002/ijc.11328
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from cancer and other causes among male airline cockpit crew in Europe

Abstract: Airline pilots and flight engineers are exposed to ionizing radiation of cosmic origin and other occupational and lifestyle factors that may influence their health status and mortality. In a cohort study in 9 European countries we studied the mortality of this occupational group. Cockpit crew cohorts were identified and followed-up in Denmark, Finland, Germany, Great Britain, Greece, Iceland, Italy, Norway and Sweden, including a total of 28,000 persons. Observed and expected deaths for the period 1960 -97 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
74
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 26 publications
11
74
1
5
Order By: Relevance
“…pilots and flight engineers) from 9 European countries showed that there was increased mortality from malignant melanoma [12]. These results were consistent at least up to the time of publication, with findings that malignant skin melanoma did occur in pilots, owing to the effects of radiation exposure.…”
Section: Malignant Melanoma (Skin)supporting
confidence: 75%
“…pilots and flight engineers) from 9 European countries showed that there was increased mortality from malignant melanoma [12]. These results were consistent at least up to the time of publication, with findings that malignant skin melanoma did occur in pilots, owing to the effects of radiation exposure.…”
Section: Malignant Melanoma (Skin)supporting
confidence: 75%
“…Several studies have reported a lower-than-expected cardiovascular mortality among flying personnel compared to the general population (1)(2)(3)(4)(5)(6)(7)(8)(9). This has many possible explanations including individual as well as occupation-related factors.…”
mentioning
confidence: 99%
“…Both the Blettner et al paper (8), which looked at 28,000 flight deck crew with 547,564 person years at risk, and the Pukkala et al paper (39), comprising 177,000 person years at risk from 10,211 pilots, concluded that occupational risk factors were of limited influence on the findings. There was consistency though in the mortality study showing an excess of malignant melanoma.…”
Section: Epidemiologymentioning
confidence: 99%
“…In Europe two large mortality cohort studies, one amongst flight deck crew (8) and one amongst cabin crew (56), together with a large cancer incidence study amongst Nordic pilots (39) have been recently published. They are based on data from many of the individual studies in the literature but contain additional data, providing increased statistical power in looking at small excesses, allow measures of consistency between studies to be determined, and provide the basis for dose-response assessments.…”
Section: Epidemiologymentioning
confidence: 99%